Radon Gas Concentration Measurement in Air of Al - Haswaa City in Province of Baghdad - Rejah, Basim Khalaf; Ashoor, Gofraan Thaar; Ashoor, Gofraan Thaar (Iraqi Journal of Science, 2022)
AbstractIn this study the radon gas concentration in air in Al - Haswaa city in province of Baghdad in Iraq have been calculated using CR-39 solid–state nuclear track detector technique. A total of 8 samples selected from 8 region in Al – Haswaa city in province of Baghdad have been placed in the dosimeters for 30 day. The average radon gas concentration was found to be 486.26 Bq/m3 which is lower than the standard international limit (1100 Bq/m3). The potential alpha energy concentration and annual effective dose have been calculated. A proportional relationship between the annual effective dose and radon gas concentration within the studied region has been certified.